Class, race and nation - Nuttall, T; Nuttall, Timothy Andrew (1991)
﻿ The 1930s and 1940s in Durban have been relatively under-researched, and yet these two decades constituted a crucial phase in the city's growth. This thesis concentrates on the political experiences of Africans during the period. The beer hall riots of 1929 and the 'African-Indian' riots of 1949 serve as significant points at which to start and end the thesis. These two flashpoints were very different in nature, and their differences signalled the changes that took place in Durban between the late 1920s and the late 1940s. Yet the riots can also be linked: they both reflected extreme frustration amongst Africans at their exclusion from the resources of the city. The two riots illuminate key issues in African politics, in municipal and state policy, and in the changing structures of Durban society. These comparative findings are based on a detailed study of the period between the two riots. A wide variety of African political experiences in Durban is examined. These fall into four broad categories of political ideology and practice: populism, nationalism, ethnicity and 'workerism'. The narrative begins with the radical anti-municipal populism of 1929-30 and then attempts to explain the politically 'quiet' 1930s. The Second World War brought significant changes, giving rise to a range of important new ideologies and political strategies. The most important developments were in worker organisation and nationalist politics. The struggle for the city was heightened even further in the post-war period. Wide-ranging expressions of urban populism and racial ethnicity set the scene for the 1949 riots. Due to the nature of the evidence collected, much of the thesis concentrates on the roles played by the (largely middle class) political leadership. The analysis portrays African politics as a complex process of 'negotiation', and the historical narrative is informed by theoretical perspectives which integrate 'class' and 'race'.